Translating Strategy into Shareholder Value. - TROTTA, Raymond J. (AMACOM, 2003)
Too often, there are serious missed signals between a company's stated goals and the methods employed to try to reach them. Translating Strategy into Shareholder Value is a unique look at how the planning process relates to the achievement of shareholder value, and ways to ensure that the two directly complement each other. Using tools and a special case study to analyze past, present, and future performance, the book takes readers through a host of steps, including: * Comparing existing strategy to the competition and the economy as a whole. * Analyzing productive capabilities and costs. * Bringing nonfinancial metrics to test how future strategy creates value. * Selecting the right analytical tool and looking at strategic solutions. If corporations are to truly maximize their success, managers need to understand how to translate corporate strategy to the bottom line -- and that means seeing the big picture.